La ronde - Schnitzler, Arthur 1862-1931; Straus, Oscar 1870-1954; Schnitzler, Arthur 1862-1931 (The Criterion Coll., 2008)
La Ronde translates as 'the round' which can refer to the policeman's beat, a circle of dancers, or a carousel, all of which this circular collection of interconnected short stories resembles. Each scene is built around a specific pair, and when one member of the pair breaks away from his or her lover, he or she then moves on to the next, introducing the partner that will lead on to the next pair, and so on until we are back where we started. Many of these lovers are seeking something they've lost in arms that look familiar but that belong to strangers. La ronde is the bittersweet note sounded by the circular nostalgia of the heart.
Aspect ratio 1.33:1. - New, restored high-definition digital transfer
Orig.: F 1950
Enth. audio commentary featuring film scholar Susan White, author of "The cinema of Max Ophuls" ; interview with Max Ophuls’s son, Academy Award–winning filmmaker Marcel Ophuls ; interview with actor Daniel Gélin ; interview with film scholar Alan Williams ; correspondence between Sir Laurence Olivier and Heinrich Schnitzler (the playwright’s son), illustrating the controversy surrounding the source play ; a new essay by film critic Terrence Rafferty
Keywords: Schnitzler, Arthur <1862-1931> -- Film and video adaptations; Schnitzler, Arthur -- 1862-1931 -- Reigen; Alltag, Brauchtum; Adultery -- Drama; Cuckolds -- Drama; Man-woman relationships -- Drama; Married women -- Drama; Mistresses -- Drama; Sex -- Drama; Vienna (Austria) -- Social life and customs -- Drama; Feature films; Fiction films; Film adaptations; Foreign films; Motion pictures, French; Video recordings for the hearing impaired; DVD